Pendampingan Operator Komputer Pada Bagian Kepegawaian Kantor Camat Praya Lombok Tengah - Hakim, Madie Wire; Pardiansyah, Ahmad S; Ashari, Maulana (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
Developments in the field of technology at this time provide a significant contribution and influence to the world of government. Management of government data such as data on employees, communities and other elements so that the process of conveying information becomes faster and more structured. With the assistance of optimizing observation activities carried out with students who get higher knowledge. The implementation method goes through several stages starting with the observation or observation stage, the activity implementation stage and the evaluation or monitoring stage. The obstacle experienced was that the participants just found out about the report, and they did not understand employee data reports. Because they are not used to only recording incoming and outgoing data that is used to achieve the many planned activities, the utilization of computer operator assistance in the personnel department is good so that it is very easy to receive important information and programs. Services are carried out informally and flexibly. Giving material begins with introducing recording and bookkeeping to participants, then also explaining the importance of ability or knowledge in implementing counselling activities. Increasing the level of understanding of computer operators about the importance of recording employee data reports in the office, utilization and use of computer resources is carried out according to the method that has been planned, namely through the stages of data collection, implementation of activities and evaluation. Participants gave positive responses to the activities that had been carried out.